Antimicrobial and Hemostatic Activities of Cotton-Based Dressings Designed to Address Prolonged Field Care Applications. (25th January 2021) - Edwards, J Vincent; Prevost, Nicolette; Yager, Dorne; Nam, Sunghyun; Graves, Elena; Santiago, Michael; Condon, Brian; Dacorta, Joseph
ABSTRACT: Introduction: Developing affordable and effective hemostatic and antimicrobial wound dressings for prolonged field care (PFC) of open wounds is of interest to prevent infection, to prevent sepsis, and to conserve tissue viability. The need for an effective hemostatic dressing that is also antimicrobial is required of a hemostatic dressing that can be left in place for extended periods (days). This is particularly important in light of the existence of pathogens that have coagulopathy properties. Thus, dressings that provide effective hemostasis and reduction in the frequency of dressing changes, whereas exerting robust antimicrobial activity are of interest for PFC. Highly cleaned and sterile unbleached cotton has constituents not found in bleached cotton that are beneficial to the hemostatic and inflammatory stages of wound healing. Here, we demonstrate two approaches to cotton-based antimicrobial dressings that utilize the unique components of the cotton fiber with simple modification to confer a high degree of hemostatic and antimicrobial efficacy. Methods: Spun bond nonwoven unbleached cotton was treated using traditional pad dry cure methods to add ascorbic acid, zeolite (NaY) with pectin, calcium chloride, and sodium carbonate/calcium chloride. Similarly, nanosilver-embedded cotton fiber was blended with pristine cotton fibers at various weight ratios to produce hydroentangled nonwoven fabrics. The resulting treated fabrics were assessed for hemostasis using thromboelastographic clotting assays and antimicrobial activity utilizing American Association of Textile Chemists and Colorists 100. Results: Zeolite-containing dressings possessed significant hemostatic activity, whereas ascorbic acid- and silver-containing dressings reduced Gram-positive and Gram-negative organism numbers by several logs. Conclusion: Based on this study, a multilayered hemostatic dressing with antimicrobial properties is envisioned. This dressing would be safe, would be economical, and have a stable shelf-life that would be conducive for using PFC.